Hasil Panen Pertama Biomassa Daun Kelor (Moringa oleifera Lam.) Setelah Pangkas Total Pada Tanaman Umur Tiga Tahun - Bambang Budi Santoso; Jayaputra Jayaputra (LPPM Universitas Mataram, 2020)
Pruning on Moringa trees aims to increase branching that affects the increase in yield of leaf biomass, and is also routinely carried out with the aim of plant performance provides benefits for ease of maintenance and harvesting as well as the sustainability of production. This pruning study aims to determine the effect of high pruning on the yield of Moringa leaf biomass in the third year of the production cycle, has been carried out in rainfed lowland rice fields. Randomly block designed trials with high pruning as a single factor, namely pruning at a height of 25 cm, 50 cm, 75 cm, and 100 cm from the ground, and was made in three replications. The results showed that the height of pruning had no significant effect on the yield of Moringa leaf biomass in the third year of the production cycle.